What I am Versus What I do: Work and identity negotiation in hyperlocal news startups. (17th August 2016) - Chadha, Monica
Abstract : As digital technologies have practically annihilated entry barriers in the field of journalism, the industry has seen the rise of many digitally native news media startups. Many of these startups are hyperlocal media, usually started by former journalists or concerned residents to provide news to their neighborhoods. Little research exists on entrepreneurship and news media and even less research exists on how these former journalists and/or concerned residents step into these new work roles and make sense of their new responsibilities. This paper explores these individuals' work-role transition and professional identity negotiation. Analyses of in-depth interviews revealed the respondents tried to make sense of their work in relation to their professional identity by melding their responsibilities with their image of who they are. Thus, they create holistic, positive, professional identities that are more reflective of their new work and roles yet not too different from their idea of who they are as professionals.